2010
DOI: 10.2754/avb201079030363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation with Rapeseed and Linseed Oil on the Composition of Fatty Acids in Porcine Muscle Tissue

Abstract: The objective of this study was to determine the effects of dietary supplementation with rapeseed and linseed oils on changes of the fatty acid profile in porcine meat. The research was conducted on 45 fattening pigs divided into three groups. Group 1 was given a diet with 2% of sunflower oil, group 2 was given a diet with 2% of rapeseed oil and group 3 was given a diet supplemented with 2% of linseed oil. The highest content of n-3 polyunsaturated fatty acids (PUFA) and the most favourable ratio of n-6/n-3 PU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
2
6
1
Order By: Relevance
“…As expected, the results of our trials indicated that there was a significant increase in α-linolenic (C18:3n-3), eicosatrienoic (C20:3n-3), and eicosapentaenoic (C20:5n-3) fatty acids in the meat of both treated groups. This agrees with the findings of Riley et al (2000), Enser et al (2000), Rey et al (2004), and Kralik et al (2010), who also indicated that dietary linseed or linseed oil supplement resulted in a significant increase of the above-mentioned fatty acids.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…As expected, the results of our trials indicated that there was a significant increase in α-linolenic (C18:3n-3), eicosatrienoic (C20:3n-3), and eicosapentaenoic (C20:5n-3) fatty acids in the meat of both treated groups. This agrees with the findings of Riley et al (2000), Enser et al (2000), Rey et al (2004), and Kralik et al (2010), who also indicated that dietary linseed or linseed oil supplement resulted in a significant increase of the above-mentioned fatty acids.…”
Section: Discussionsupporting
confidence: 92%
“…However, it should be noted that no significant differences for the docosahexaenoic (C22:6n-3) fatty acid were found in our study between the treated and control groups, notwithstanding the intake of linseed oil sediment. This agrees with the findings of Riley et al (2000), Wood et al (2003), and Václavková and Bečková (2007), who supplemented pig feed with linseed or linseed oil, but contradicts the findings of Cunnane et al (1990), Enser et al (2000), and Kralik et al (2010), who reported a significant increase of C22:6n-3 in the meat.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations